THE EFFECT OF HYDROGEN PRESSURE ON THE PREPARATION OF ARTIFICIAL CAKING COAL FOR COKE BINDER - NINING S. NINGRUM; Miftahul Huda; HERMANU PRIJONO (Puslitbang tekMIRA, 2011)
Binder of carbon compounds can be made through hydrogenation process and/or coal extraction. Hydroge- nation of coal converts the steam coal into caking one which functions as a binder or additive in the making of coke while the extraction of coal produces good quality pitch. Some coals from Tanito Harum, Baramarta and Bukit Asam were used as raw materials for binder making. Observations included effect of hydrogen pressure on the total carbon and ash contents and free swelling index as well. Coal hydrogenation was performed in a 5-litre batch type autoclave at reaction temperature of 400oC. The initial hydrogen pressure varies from 5 to 30 bars and to 1 hour reaction time. The next stage was the distillation of hydrogen product. It can be concluded that all non-caking coals used in the experiments can be converted into caking coal to be used as a binder in the coke making. The ash content within coal considerably affects the resulting binder product; binder that has low ash content is preferred.